National Center Contribution Processing Data Center Of GNSS Retention of The Land International Framework - Moya Zamora, Jorge (2016)
The Centro Nacional de Procesamiento de Datos GNSS (CNPDG) of Escuela de Topografía, Catastro y Geodesia (ETCG), Universidad Nacional (UNA) is a laboratory conducting the scientific weekly processing of a sector of GNSS stations continuously measuring network belonging to Sistema Geocéntrico para las Américas (SIRGAS). This network consists of 89 stations located in countries like United States, Mexico, Guatemala, El Salvador, Honduras, Nicaragua, Costa Rica, Colombia, Panama and Brazil (Sirgas, 2014). The CNPDG formally began work in January 2013 as a center for experimental processing. In early 2014, the formalization is given by SIRGAS and then when the CNPDG first processing center GNSS data Central America and the Caribbean became. This document is to show the scientific processing of a GNSS network of continuous observation and weekly results, which once integrated and combined with the results of the remaining processing centers SIRGAS the continent, represent a direct contribution to the maintenance of International Terrestrial Reference Frame (ITRF). The processing of this type follows a series of internationally standardized technical criteria recommended by the International Association of Geodesy (IAG). The calculation Bernese specialized software version 5.2 allows contemplate a lot of variables and apply different models to obtain high accuracy results. The so-called semi-free solutions have been generating since CNPDG come from the GPS 1721 (beginning January 2013) a week 1790 (end of May 2014) week. The CNPDG is also a space for the work of students and the development of activities, research projects and final graduation work